Causal association between cardiovascular diseases and erectile dysfunction, a Mendelian randomization study - Li, Qingying; Long, Qiang; Ren, Baoming; Bing, Sen (Frontiers in Cardiovascular Medicine, 2023)
Background: Cardiovascular diseases (CVD), including coronary heart disease (CHD), heart failure, ischemic heart disease (IHD), and atrial fibrillation, are prevalent in the aged. However, the influence of CVD on ED is less investigated. To clarify the causal association between CVD and ED, this study was performed. Materials and Methods: Genome-wide association studies (GWAS) datasets targeting CHD, heart failure, IHD, and atrial fibrillation were downloaded to retrieve the single nucleotide polymorphisms (SNPs). Further, single variable Mendelian randomization and multivariable Mendelian randomization (MVMR) were adopted to explore the causal association between CVD and ED. Results: Genetically predicted CHD and heart failure were found to increase the risks of ED (OR = 1.09, P < 0.05 & OR = 1.36, P < 0.05, respectively). However, no causal association was disclosed between ischemic heart disease, atrial fibrillation and ED (all P > 0.05). These findings remained consistent in sensitivity analyses. After controlling for body mass index, alcohol, low density lipoprotein, smoking and total cholesterol levels, the results of MVMR support the causal role of CHD on ED (P < 0.05). Similarly, the direct causal effect estimates of heart failure on ED were also significant in MVMR analyses (P < 0.05). Conclusion: Using genetic data, this study discloses that genetically predicted CHD and heart failure can causally increase the risk of ED, while atrial fibrillation, and IHD can’t.